Identification of new molecular targets for PET imaging of the microglial anti-inflammatory activation state - Alessandro Villa; Barbara Klein; Bieneke Janssen; Jordi Pedragosa; Giovanna Pepe; Bastian Zinnhardt; Danielle J. Vugts; Paolo Gelosa; Luigi Sironi; Wissam Beaino; Annelaure Damont; Frédéric Dollé; et al. (IVYSPRING INT PUBL, 2022)
Microglia are potential targets for therapeutic intervention in neurological and neurodegenerative diseases affecting the central nervous system. In order to assess the efficacy of therapies aimed to reduce the tissue damaging activities of microglia and/or to promote the protective potential of these cells, suitable pre-clinical and clinical tools for the in vivo analysis of microglia activities and dynamics are required. The aim of this work was to identify new translational markers of the anti-inflammatory/protective state of microglia for the development of novel PET tracers.
Methods: New translational markers of the anti-inflammatory/protective activation state of microglia were selected by bioinformatic approaches and were in vitro and ex vivo validated by qPCR and immunohistochemistry in rodent and human samples. Once a viable marker was identified, a novel PET tracer was developed. This tracer was subsequently confirmed by autoradiography experiments in murine and human brain tissues.
Results: Here we provide evidence that P2RYI2 expression increases in murine and human microglia following exposure to anti-inflammatory stimuli, and that its expression is modulated in the reparative phase of experimental and clinical stroke. We then synthesized a novel carbon-II labeled tracer targeting P2RYI2, showing increased binding in brain sections of mice treated with IL4, and low binding to brain sections of a murine stroke model and of a stroke patient.
Conclusion: This study provides new translational targets for PET tracers for the anti-inflammatory/protective activation state of microglia and shows the potential of a rationale-based approach. It therefore paves the way for the development of novel non-invasive methodologies aimed to monitor the success of therapeutic approaches in various neurological diseases.